2018
DOI: 10.1038/s41598-018-27318-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptome analysis of dikaryotic mycelia and mature fruiting bodies in the edible mushroom Lentinula edodes

Abstract: Lentinula edodes is a popular cultivated edible mushroom with high nutritional and medicinal value. To understand the regulation of gene expression in the dikaryotic mycelium and mature fruiting body in the commercially important Korean L. edodes strain, we first performed comparative transcriptomic analysis, using Illumina HiSeq platform. De novo assembly of these sequences revealed 11,675 representative transcripts in two different stages of L. edodes. A total of 9,092 unigenes were annotated and subjected t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 61 publications
5
48
0
Order By: Relevance
“…Of the fungal cell wall (FCW) associated genes, hydrophobins were mostly developmentally regulated (eight of 11 genes) in A. ampla (Fig. S3), often with significantly increased expression coincident with the transition from vegetative mycelium to Stage 1 primordia (in six genes), as observed previously (van Wetter et al ., , ; Banerjee et al ., ; Ohm et al ., ; Song et al ., ). Several members of two functionally similar families, cerato‐platanins (4 of 5 genes dev.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Of the fungal cell wall (FCW) associated genes, hydrophobins were mostly developmentally regulated (eight of 11 genes) in A. ampla (Fig. S3), often with significantly increased expression coincident with the transition from vegetative mycelium to Stage 1 primordia (in six genes), as observed previously (van Wetter et al ., , ; Banerjee et al ., ; Ohm et al ., ; Song et al ., ). Several members of two functionally similar families, cerato‐platanins (4 of 5 genes dev.…”
Section: Resultsmentioning
confidence: 97%
“…These genes showed 254‐ and 855‐fold upregulation in Stage 1 primordia of both A. ampla and S. commune , respectively, and had high expression in all fruiting body tissues (> 5000 FPKM, maximum fold change within fruiting bodies 3.4–3.7), suggesting an important role of heat shock proteins during fruiting body development. In further support of this hypothesis, homologs of these genes were found to be developmentally regulated or differentially expressed also in Laccaria bicolor fruiting bodies (Martin et al ., ), Lentinula edodes (Song et al ., ) , Armillaria ostoyae, Coprinopsis cinerea, Lentinus tigrinus and Rickenella mellea (Krizsán et al ., ). Another co‐ortholog with significant upregulation in Stage 1 primordia included A1 aspartic proteases, although the expression dynamics were somewhat different in the two species.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When combined with the results of the KEGG pathway analysis of the DEGs, this indicated that functional groups were associated with vitamin B6 metabolism, glycine metabolism, and cystathionine lyase, which might play an important role in LIPF in S. latifolia. Metabolism of vitamins was also involved in fruiting body formation in Lentinula edodes [37].…”
Section: Discussionmentioning
confidence: 99%
“…SYBR green-based qRT-PCR was performed using FastStart Essential DNA Green Master mix (Roche, Basel, Switzerland) on a LightCycler 96 system (Roche). Statistical analysis of viral gene expression were calculated via the comparative threshold cycle method using the LightCycler 96 qualitative detection module (Roche), as described previously 42 . In addition, relative gene expression levels of target genes in the mycelia, fruiting bodies, and sawdust spawn were performed with the same qRT-PCR method for the viral gene.…”
Section: Methodsmentioning
confidence: 99%